The reasonableness and feasibility of replacing standing wave vibration with air piston mode vibration in thermoacoustic refrigerator - Jianxin Wang; Xiangbin Liu (Heliyon)
On the basis of analyzing the longitudinal forced vibration of the gas column in the resonator of a half-wavelength standing wave thermoacoustic refrigerator, the idea of replacing the standing wave vibration with the first-order piston mode vibration of the gas column in the thermoacoustic refrigerator was proposed, so as to increase the vibration amplitude of the gas in the resonator, realize the large alternating flow of gas, and improve the working efficiency of the thermoacoustic refrigerator. At the same time, its rationality and feasibility are discussed from the aspects of modal vibration, pressure distribution of gas column piston, and temperature variation of gas microcluster vibration in equilibrium position. Combined with the existing research results, the superiority of the application of the first-order piston mode vibration of the gas column in the thermoacoustic refrigerator is further explained. The results provide a new research idea and direction for further reducing the cold end temperature of thermoacoustic refrigerator.